Optimized Kinetics Match and Charge Balance Toward Potassium Ion Hybrid Capacitors with Ultrahigh Energy and Power Densities. Issue 42 (28th September 2020) - Peng, Yufan; Zhang, Rui; Fan, Binbin; Li, Weijian; Chen, Zhen; Liu, Hui; Gao, Peng; Ni, Shibing; Liu, Jilei; Chen, Xiaohua
Abstract: Potassium ion hybrid capacitors (PIHCs) are of particular interest benefiting from high energy/power densities. However, challenges lie in the kinetic mismatch between battery‐type anode and capacitive‐type cathode, as well as the difficulty in achieving optimized charge/mass balance. These significantly sacrifice the electrochemical performance of PIHCs. Here, strategies including charge/mass balance pursuance, electrolyte optimization, and tailored electrode design, are employed, together, to address these challenges. The key parameters determining the energy storage properties of PIHCs are identified. Specifically, i) the good kinetic match between anode and cathode translates into the very small variation of cathode/anode mass ratio at various rates. This sets general rules for the pursuance of charge balance, and to maximize the electrochemical performance of hybrid devices. ii) A potassium bis(fluoroslufonyl)imide (KFSI)‐based electrolyte promotes better electrode kinetics and allows for the formation of more stable and intact solid electrolyte interphase layer, with respect to potassium hexafluorophosphate (KPF6 )‐based electrolyte. And iii) hierarchically porous N/O codoped carbon nanosheets (NOCSs) with enlarged interlayer spacing, disordered structure, and abundant pyridinic‐N functional groups are advantageous in terms of high electronic/ionic transport dynamics and structural stability. All these together, contribute to the high energy/power density of the activated carbon//NOCSs PIHCs (113.4 Wh kg −1, at 17, 000 W Kg −1 ). Abstract : An integrated strategy consisting of charge/mass balance pursuance, electrolyte optimization, and tailored‐electrode design, is proposed to boost the electrochemical performance of potassium ion hybrid capacitors (PIHCs). The key parameters that determine the energy‐storage behavior are identified, and the general rules for high‐performance PIHCs design are proposed. This work provides a better fundamental understanding and invaluable guidance for high‐performance hybrid energy‐storage device design.